THE RELATIONSHIP BETWEEN THE LEVEL OF MOTHER'S KNOWLEDGE OF PENTABIO IMMUNIZATION (DPT- HB- HiB) AND MOTHER'S ANXIETY TOWARD EFFECT OF GIVING IMMUNIZATION ON INFANTS IN POLYCLINIC OF DAGEN VILLAGE JATEN KARANGANYAR - Idris Yani Pamungkas; Fitri Budi Astuti; Irwiana Budi Astuti (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2016)
Background: According to WHO, the figures for DPT immunization globally was 78%, it means there are 28 million children in the world who have not got DPT immunization. 75% of these children live in 10 countries, including Indonesia. Data cumulative achievement of Pentabio immunization (DPT- HB- HiB) in Dagen village on December 2014 was DPT- HB- HiB 1 was 80%, DPT- HB- HiB 2 was 72, 9%, and DPT- HB- HiB 3 was 74, 1%. From a preliminary study conducted by researchers in Dagen village through doing interviews, it can be stated that some parents as young mothers who first have children still worried and confused because the child became fussy fever after getting DPT immunization which is now known as Pentabio immunization , although after having immunization they have been given fever medicine. Objective: in order to determine the relationship between the level of mother's knowledge of Pentabio immunization (DPT- HB- HiB) and mother's anxiety toward effect of giving immunization on infants in polyclinic of Dagen village Jaten Karanganyar Methods: this research method was correlational. The approaching method was cross sectional. The population was all infants and their parents in Dagen village with certain characteristics to be studied. The Sampling techniques was purposive sampling. the analysis of data was Kendall's Tau. Results: The results showed that there was correlation of between the level of mother's knowledge of Pentabio immunization (DPT- HB- HiB) and mother's anxiety toward effect of giving immunization on infants in polyclinic of Dagen village Jaten Karanganyar. (p value: 0,000) Conclusion: The increased knowledge of the mother is still needed to improve information related to Pentabio immunization giving with mother's anxiety toward the side effects of Pentabio immunization on infants so much more anticipation of the risks that will happen.